Pendekatan Psikologi Dalam Penanganan Korban Kekerasan Seksual Terhadap Perempuan Dan Anak - Haryati, Haryati; Sahidun, Nurfitri; Nihi, Sriyanti (AL-WARDAH: Jurnal Kajian Perempuan, Gender dan Agama, 2022)
The purpose of this study is to identify the psychological strategy for treating victims of sexual assault of women and children. In recent years, there has been a rise in sexual assault against women and children. Anyone, anywhere, at any moment, can experience violence. Sexual assault victims typically endure more stress in the aftermath of the cruel act, followed by feelings of unfairness, unhappiness, or physical, sexual, and psychological pain. As a result, the victim withdraws from her social circle, making it challenging for her to maintain her social life. Because the function of the family and society is to give women and children a sense of security, encouragement from specific families and communities is vital. giving victims a sense of security.Treatment that actually restores or cures victims from traumatic sensations through a psychological approach, such as rehabilitation (the recovery process), therapy, and others, goes hand in hand with giving victims a sense of security. The research method employed is a descriptive literature study, and the sources of the data used were books, websites, journals, and previous studies.